Sport Psychophysiology: The Current Status of Biofeedback with Athletes (Part 1) - Leonhard, J. (Biofeedback, 2003)
This article is the first in a threepart series on the use of biofeedback (BFB) in helping athletes reach their optimal competitive potential. The author`s extensive literature review suggests that however compelling the outcomes, research in this area has been surprisingly quite limited. Perhaps chiefly responsible for the lack of growth in this field, a field considered otherwise fraught with potential, has been inconsistent methodology, which at times has bordered on little more than untested assumptions. Happily, studies today seem increasingly rigorous, the findings more empirically robust, leaving little doubt that research in this field can pass scientific muster. The author is thereby optimistic that this new field, which he refers to as sport psychophysiology (SPP), could eventually achieve recognition as distinct yet complementary to the myriad other established disciplines making up the sports sciences. Such an achievement would certainly augur well for a new generation of applied and research-oriented BFB enthusiasts. In short, this three-part series will review the trends, problems, and ultimately the potential for SPP as an applied science in its own right. In dem gleichen Heft auch folgender Artikel: Surface EMG and the Evolution of Aquatic Biofeedback (Ron Fuller) The union of aquatic therapy and surface EMG was derived out of necessity in order to help validate the effects of aquatic therapy exercise and to qualify its outcomes. The technique of aquatic biofeedback has undergone several changes in its evolution. Initially, waterproofing the electrode was done with a bioclusive barrier that was expensive and difficult to apply. Now, with the advent of a latex extremity sock that covers the electrode, application of the technique is much easier and less time consuming. The aquatic biofeedback technique is currently being used in the treatment of orthopedic and neurologic conditions, such as cerebral vascular accidents (CVA`s), anterior cruciate ligament repairs, patellofemoral pain syndrome (PFPS) and spinal cord injuries.